Defining conversion therapy for esophageal squamous cell carcinoma. Issue 1 (19th October 2022) - Matsuda, Satoru; Tsushima, Takahiro; Kato, Ken; Hsu, Chih‐Hung; Lee, Jang Ming; Wong, Ian Yu‐Hong; Wang, Hu‐Lin Christina; Kang, Chang Hyun; Guo, Xufeng; Yamamoto, Shun; Tsuji, Takayuki; Kawakubo, Hirofumi; et al.
Abstract : A multimodality treatment conference with experts from across East Asia was held to establish a consensus for conversion therapy. An agreement was reached that conversion therapy was defined as surgery or chemoradiotherapy (CRT) aiming at cure after initial treatment for tumors that were initially unresectable due to adjacent organ invasion or distant metastasis.